2007
DOI: 10.1093/aob/mcm248
|View full text |Cite
|
Sign up to set email alerts
|

Xyloglucan Endotransglucosylase Activity Loosens a Plant Cell Wall

Abstract: The results provide evidence that XTHs can act as cell wall-loosening enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
147
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(155 citation statements)
references
References 55 publications
7
147
0
1
Order By: Relevance
“…These results suggest that alteration of fruit characteristics in transgenic tomatoes was due to the increase or reduction of cell enlargement by the alteration of SlXTH1 gene expression, since during the period before flowering, the cells stop undergoing cell division and all later growth of fruits is associated entirely with cell enlargement. The data thus provide further evidence for the in vivo role of XTH proteins in causing cell wall loosening and hence cell expansion (van Sandt et al 2007). …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These results suggest that alteration of fruit characteristics in transgenic tomatoes was due to the increase or reduction of cell enlargement by the alteration of SlXTH1 gene expression, since during the period before flowering, the cells stop undergoing cell division and all later growth of fruits is associated entirely with cell enlargement. The data thus provide further evidence for the in vivo role of XTH proteins in causing cell wall loosening and hence cell expansion (van Sandt et al 2007). …”
Section: Discussionmentioning
confidence: 60%
“…This suggests that XTH controls the yield threshold of cell enlargement by modulating the size of the polysaccharide cluster (Cosgrove 1997), but does not introduce loosening or extension of the wall. However, expression of XTH genes has been correlated with cell expansion in a variety of tissues (Cui et al 2005;Feng et al 2008;Hyodo et al 2003;Shin et al 2006;Yun et al 2005), and addition of active XET protein was shown to cause cell wall loosening in vivo in onion epidermal cells (van Sandt et al 2007). This suggests that in certain tissues and under certain circumstances, XET activity may be involved in wall loosening.…”
mentioning
confidence: 99%
“…Growth cessation is also observed in Haberlea during drought and desiccation, which is in line with the morphological observations and the downregulation of many cell wall-related genes, including several expansins and xyloglucan endotransglucosylases. In Arabidopsis, these genes participate in cell expansion and growth by loosening the cell wall [48]. Likewise, downregulation of cell wall growth and photosynthesis-related genes were observed during a recent transcriptomic analysis of two near-isogenic rice lines with different levels of drought tolerance [49].…”
Section: Discussionmentioning
confidence: 89%
“…In more detail, the average cell area within the base, middle and top zones of the GFP-TUA6 leaf was systematically lower in UV-treated leaves from 8 days after UV-exposed and control plants of Lactuca sativa L. 7 and Pisum sativum 8 could be observed, reinforcing the idea that especially the modulation of cell wall properties is the main factor causing the observed UV-induced reduction in cell expansion. Some reports indicate differential expression of wall loosening enzymes like expansins or xyloglucan endotransglycosylase/hydrolases (XTHs), 9,10 or cell wall strengthening enzymes as particular peroxidases 7 after UV exposure. Another key event could involve UV-mediated changes in the phenylpropanoid pathway, which may cause changes in the lignin biosynthesis.…”
mentioning
confidence: 99%